Efektivitas Modul Ajar menggunakan Model Pembelajaran POE untuk Meningkatkan Keterampilan Proses Sains Peserta Didik - Rosalina, Amalia; Miriam, Sarah; Qamariah (Universitas Sarjanawiyata Tamansiswa, 2024)
Science process skills are essential for students in physics learning, but their current abilities are still considered inadequate. This inadequacy is due to the lack of teaching modules designed to enhance these skills. Therefore, this study developed a teaching module using the Predict, Observe, Explain (POE) learning model to improve students' science process skills. The research follows the Research & Development (R&D) approach with the ADDIE development model, producing both qualitative and quantitative descriptive data. The subjects were 30 students from class XI A at SMAN 10 Banjarmasin. The instrument used was a science process skills test sheet, and the analysis technique employed was the N-gain score. The results showed that the teaching module using the POE learning model effectively improved students' science process skills, with an N-gain score of 0.41, categorized as moderate. Thus, it can be concluded that the teaching module using the POE learning model is effective for enhancing students' science process skills.